Acute Encephalopathy and Refractory Hypokalemia in a 12-Year-Old Boy - Moosavian, Toktam; Pournasiri, Zahra; Fatollahierad, Shiva (Iranian Journal of Child Neurology, 2025)
Wilson disease is an inherited disorder characterized by copper accumulation in various organs, leading to a wide range of clinical manifestations depending on the deposition site. Typically, symptoms of Wilson disease emerge between the ages of 5 and 35 years, primarily presenting with neurological and hepatic symptoms. This case report describes a 12-year-old boy diagnosed with Wilson disease based on low serum ceruloplasmin levels and elevated 24-hour urinary copper levels. His initial presentation included acute encephalopathy and tubulopathy with persistent hypokalemia. This case highlights the importance of a thorough evaluation, including neurological and renal assessments, to determine the underlying cause of acute encephalopathy, such as Wilson disease. Furthermore, this case shows that Wilson disease can manifest with neurological and kidney presentations despite a normal hepatic evaluation.